2020
DOI: 10.31219/osf.io/ck9y4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Friendship networks and academic motivation: A longitudinal investigation examining selection and influence processes in adolescents

Abstract: Friends are sometimes similar in their academic motivation. The current study examines the mechanisms underlying similarity by disentangling selection and influence processes in adolescent friendship networks, using longitudinal data. A total of 495 adolescents from an independent school for girls were assessed for their academic motivation (including perceived competence, interest, boredom, autonomous motivation, grit, mindset and value) and social network information, annually, for 3 years. Stochastic actor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some researchers have found evidence of both selection and influence. For example, Stark et al (2017) found both selection and influence for academic achievement in a sample of 13-year-old German students, and Burgess et al (2020) similarly found both selection and influence effects for United Kingdom adolescent girls. In contrast, other researchers have found only selection or only influence.…”
Section: Academic Selection and Influencementioning
confidence: 96%
See 1 more Smart Citation
“…Some researchers have found evidence of both selection and influence. For example, Stark et al (2017) found both selection and influence for academic achievement in a sample of 13-year-old German students, and Burgess et al (2020) similarly found both selection and influence effects for United Kingdom adolescent girls. In contrast, other researchers have found only selection or only influence.…”
Section: Academic Selection and Influencementioning
confidence: 96%
“…Most SIENA studies of peers and academic adjustment have been conducted within single small networks with students from the same grade (e.g., Fortuin et al, 2016;Shin & Ryan, 2014a, 2014bStark et al, 2017). Although some researchers have included both middle and high school students in their samples (e.g., Burgess et al, 2020;Flashman, 2012), none of the researchers differentiated between middle and high school or examined age moderation. There have been many studies, however, of peer conformity and influence processes as a function of age that can inform predictions of whether academic selection and influence differs for middle and high school students.…”
Section: Age and Selection And Influencementioning
confidence: 99%
“…Nevertheless, a study on a sample of students in a girls' school in the United Kingdom found that both a growth mindset and perseverance were influenced by friends and also played a role in selecting friendships. In contrast, the overall value of learning was only a significant factor in friendship selection (Burgess et al, 2020).…”
Section: How Educational Aspirations and Academic Achievement Can Con...mentioning
confidence: 91%